SYNTHESIS, CHARACTERIZATION AND APPLICATIONS OF MODIFIED NANOCLAY SUSPENSION FROM KAKURI VILLAGE - Asseh, Emmanuel; Azeh, Yakubu; Musa, Mohammed (FUDMA JOURNAL OF SCIENCES, 2024)
In this study, the preparation of modified nanoclay using different amino acids has been investigated. The modified and unmodified nanoclay sample has been characterized using X- Ray Diffraction (XRD), Brunauer-Emmett Teller   (BET), Particle Size and Scanning Electron Microscopy (SEM). The XRD results suggest that the interlayer spacing of modified nanoclay increases with the intercalation of the modifiers. BET showed that nanoclay was successfully synthesized as revealed by the pore width and volume in the range of 2.647-45.23nm and 11.08-862.6cm3/g, with a BET surface area of 262.1m2/g for the control (CTL). Whereas, Arginine, Tyrosine and Aspartic acid modified nanoclay had 1.847-6.503nm, 2.647-45.23nm and 2.647-45.23nm each with a BET SA of 533.9, 325.4 and 356.3m2/g respectively. Study revealed that the clay deposits were composed of a mixture of clay minerals (Quartz,  Anorthite,  Kaolinite, Montmorillonite, Orthoclase and Muscovite). Particle size shows that unmodified nanoclay had particle diameter in the range of 0.88-68.71nm, Whereas, modified nanoclay sample had particle size value of 0.88-60.52nm for TYS, ASP and ARG respective. SEM images revealed the presence of varying pore sizes distribution across the surface area of both the modified and unmodified nanoclay samples.
Keywords: Synthesis; Nanoclay; Modification; Characterization; Antimicrobial